Enhancing learning and character through NHT model in grade x culinary class at SMKN 4 Yogyakarta - Badraningsih Lastariwati; Titin Hera Widi Handayani; Miftakhul Wahniyatun; Duani Pangestu; Enggar Ristyorini; Fendi Tri Hatmoko (Faculty of Engineering, Universitas Negeri Yogyakarta, 2025)
The purpose of the research is to improve learning outcomes and strengthen student character. This research is a Classroom Action Research designed with the Kemmis & McTaggart model. The subjects of the research were 36 students of class X majoring in Culinary Arts. The research instrument used multiple choice questions, student character observation sheets. Data collection techniques used observation, tests, documentation. Data analysis techniques used descriptive data for learning outcomes and qualitative descriptive statistics for observation of student character. The sequence of Numbered Head Together learning is (a) Numbering, (b) Teacher gives assignments, (c) Discussing and reporting the results of the discussion, (e) Responses from other friends, and (f) Conclusions. The learning outcomes of students in stage E of the subject of Basic Culinary Arts of class X Culinary Arts 6 showed that students who achieved the Minimum Completion Criteria in Cycle I and Cycle II were 24 students with 67% of students and 34 students with a percentage of 94%. The observation results of the Global Diversity dimension were 68% in Cycle I and 78% in Cycle II. In the Gotong Royong dimension, it was 71% in Cycle I and 80% in Cycle II. Both dimensions are in the good category. The conclusion of this study is that efforts to improve learning outcomes and strengthen students' characters by implementing NHT show positive results. Strengthening character must continue to be supported and implemented with various learning models other than NHT